Inverting a non-major’s biology class: Using video lectures, online resources, and a student response system to facilitate deeper learning - Jayson Elliott Lloyd (Journal of Teaching and Learning with Technology, 2014)
Using pre-recorded video lectures, online resources, and a student response system (iClicker), instructors attempted to facilitate deeper learning in a non-major’s biology class. Following an inverted classroom format, students viewed lecture videos and completed online activities prior to face-to-face meetings with instructors. During face-to-face (traditional “lecture”) time, instructors tested student knowledge and guided students in group activities. Using a quasi-experimental design, researchers compared student performance on a comprehensive final exam with student performance from a previous semester. An independent sample t test indicated that students engaged in the inverted instructional model (N = 73, M = 74.49, SD = 12.54) performed better than students engaged in a traditionally model of instruction (N = 76, M = 70.32, SD = 12.19), t(147) = 2.06, p = 0.02. The effect size for this analysis (d = 0.33) represents a small effect according to Cohen (1988). Researchers also performed a chi-square test of goodness-of-fit to determine if grade distributions from the inverted model differed from the traditional model. Grade distributions from the inverted model were significantly different, X2 (5, N=100) = 24.85, p < .05.